Improve Hot Mixed Asphalt Using Polypropylene Fiber - سلطان بسام; مرشد مجد (Latakia University Journal -Engineering Sciences Series, 2021)
Asphalt layers suffer from problems and defects such as fatigue cracks, reflexive cracks and rutting problems. Therefore, these common problems must be addressed. The addition of fibers is considered one of the methods used to improve the properties of asphalt mixtures in terms of improving the hardness of materials, increasing their resistance to fatigue, and improving mechanical properties. This research aims at the possibility of improving asphalt mixtures by adding polypropylene fibers (PPF) to asphalt mixtures, and studying the effect of adding them on the performance of asphalt mixtures through laboratory study, including designing a conventional asphalt mixture according to the Marshall method and then adding ratios that include (0.2 - 0.3) - 0.5%) by weight of the asphalt mixture with a fixed length of polypropylene fibers and studying the volumetric properties of the designed mixtures and both the stability and flow of Marshall at each addition percentage and the corresponding properties. Results showed that the optimum asphalt content for the reference mixture according to the Marshall method is (5.0%), and that the optimum percentage of addition of fibers is (0.3%). It is considered an optimum ratio to add polypropylene fibers with a length of (5 mm) to be used in modifying the properties of the asphalt mixture as it meets the requirements of asphalt mixtures while achieving an increase in stability and a decrease in flow.